PENGARUH KOMPETENSI, KOMPENSASI, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DIREKTORAT JENDERAL PERIMBANGAN KEUANGAN, KEMENTERIAN KEUANGAN RI - Irawan Wijaya; Yoyoh Rohaniah (KELOLA: Jurnal Ilmiah Manajemen, 2021)
This study aims to examine the effect of competence, compensation, and motivation on employee performance at the Directorate General of Fiscal Balance, Ministry of Finance in Jakarta. This research belongs to the type of correlative research where this research seeks to find a relationship between the competency, compensation, and motivation variables on employee performance variables. The population in this study were employees who had worked at the Directorate General of Fiscal Balance, Ministry of Finance of the Republic of Indonesia with a total sample of 60 people. The results of this study found that the competency variable has a partial and significant effect on employee performance or in other words, hypothesis 1 can be accepted. Compensation variable has a partial and significant effect on employee performance, or in other words, hypothesis 2 can be accepted. Motivation variable has a partial and significant effect on employee performance or in other words, hypothesis 3 can be accepted. Competency, Compensation and Motivation variables have a joint or simultaneous and significant effect on employee performance or in other words, hypothesis 4 can be accepted